Effects of a combined nature-based and audio-based virtual mindfulness intervention on stress and wellbeing of COVID-19 healthcare workers: a randomized controlled trial - Polycarpe Bagereka; Rezvan Ameli; Ninet Sinaii; Marcelli Cristine Vocci; Angelina Mangiardi Coulter; Michael Neustedter; Ann Berger (PeerJ)
Background The global COVID-19 pandemic and its subsequent transition to an endemic phase has highly increased psychosocial distress among healthcare workers. This chronic stress may culminate into burnout, which has been associated with impaired patient care and increased medical errors. Exposure to nature-based programs have been shown to reduce levels of perceived stress and promote well-being. However, benefits derived from nature programs can be short-lived. Mindfulness-based interventions represent a promising additive option to enhance benefit. The present study proposes to combine a nature-based program with an audio-based mindfulness intervention to address stress and promote psychosocial-spiritual wellbeing in COVID-19 healthcare workers. Methods Between June 2021 and October 2023, 78 healthcare workers were randomized into a Nature only group (Nature), a Combined Nature-Mindfulness group (Combined), and a control group (Control), with 19, 16, and 18 subjects completing the study, respectively (23–46 years, mean = 35, SD = 6). The nature program was a three or five-day retreat during which participants engaged in rock climbing, surfing or kayaking. The virtual audio mindfulness intervention was a 10-day program offered online and included mindful breathing, body scan, and loving-kindness meditation. Participants completed self-administered assessments at three or four time points during the study, including at baseline and following study procedures. Assessments included a measure of stress, the Perceived Stress Scale, and a measure of wellbeing, the National Institute of Health Healing Experience of All Life Stressors (NIH-HEALS). Results The mean baseline Perceived Stress Scale score was 21.2 ± 3.2 in the Combined group, 22.3 ± 2.8 in the Nature group, and 23.2 ± 3.3 in the Control group. Perceived Stress Scale levels did not change following nature-based and mindfulness-based interventions. The mean baseline NIH-HEALS score was 123.1 ± 19.4 in the Combined group, 118.1 ± 17.1 in the Nature group, and 114.3 ± 17.8 in the Control groups. NIH-HEALS scores increased in both the Nature and Combined groups when compared to the Control group. At follow-up, the Combined group maintained improvements in wellbeing when compared to the Nature group. Conclusions Findings suggest that nature-based programs can be used to improve overall wellbeing among COVID-19 healthcare workers. Additionally, integrating audio-based mindfulness practices to these programs may enhance their benefits. Notably however, these interventions may not effectively reduce perceived stress among COVID-19 healthcare workers. Due to diminished power of the present study, further research is needed to validate and refine the present findings.